Desain dan Implementasi Kendali Digital Proportional-Integral pada Cuk Converter - Wibisono, Arifin; Riyadi, Slamet; Martanio, Alvin (Majalah Ilmiah Teknologi Elektro, 2022)
DC-DC converter are required in industrial application to convert a fixed DC voltage into a variable DC voltage. This article focuses on the cuk converter topology which can operate in buck-boost mode which is regulated through the duty cycle pulse width modulation setting and controlled by the dsPIC33EP512MU810 microcontroller by applying the Proportional-Integral (PI) digital closed loop current control method. Using PI control method is considered capable of producing optimal performance and increasing the response time that occurs. The frequency given by the generator signal is used as a reference signal to inject current into the inductor (L1). The current sensor module acts as a measuring device and a reader of the actual current value that appears through the load. The difference between the reference current value and the actual value will produce an error signal value so that it becomes the comparison value of the current sensor results with the PI control method. Simulation results on PSIM, modeling analysis, device implementation and hardware testing graphs in the laboratory have been carried out to prove the design parameters and proposed methods can work as intended.